PENGARUH BERBAGAI MACAM DAN DOSIS BAHAN TAMBAHAN TERHADAP KADAR BAHAN KERING DAN ASAM LAKTAT SILASE RUMPUT PADANG GOLF - Utomo, Dzulfikar Satrio; Hendarto, Eko; Widiyastuti, Titin (ANGON: Journal of Animal Science and Technology, 2021)
Background. The purpose of this research is to study the effect of various kind and dose on dry matter and lactic acid content in golf course grass silage. Materials and methods. The material of this research is ± 135 kg of golf course grass, ± 2,5 kg of for each additive, which is cassava, sweet potato, and rice bran. The research conduct on March 26 until April 28, 2021 at Wijayakusuma Purwokerto Golf Course, Greenhouse Experimental, Agrostology Laboratory of Animal Science Faculty, and Food Technology Laboratory of Jenderal Soedirman University, Purwokerto. The research used the experimental method with a complete randomized design (CRD), with 7 treatments and 3 replications and followed by contrast orthogonal test. Results. The results of analyze showed that the various kind and dose of additive are have a very significant effect (P<0,01) on dry matter and lactic acid content in golf course silage. Conclusion. The conclusion of this research is the various kind of additive effected the dry matter and lactic acid content in silage. The various dose of additive not effected the dry matter content, but the addition of rice bran and cassava effected the lactic acid content in silage. The addition of rice bran as an additive for making a silage is very effective to increase the dry matter and lactic acid content.